The Meaning of Fasadu in QS. Ar-Ruum [30]: 41; Semiotic Analysis of Roland Barthes - Muhammad Aziz; Supriadin Supriadin (Spiritus: Religious Studies and Education Journal, 2024)
The phenomenon of demage on earth both on land and in the ocean carried out by human hands has disturbed living things and their surroundings. Basically, this phenomenon has occured since ancient times until today. Whereas Allah has warned regarding the demage in QS. Ar-Ruum: [30]; 41, therefor it is necessary to understand the word structure contained in the verse so that damage can be prevented. This article aims to reveal how Roland Barthes semiotics analyzes QS. Ar-Ruum [30]: 41 and how the meaning of the word fasadu QS. Ar-Ruum [30]: 41 explained in several books of interpretation? To answer these questions, the author uses the literature study method using the Roland Barthes semiotic approach. The result of this research is that according to the linguistic system, it is a person who does damage. While the connotation meaning is people who do damage to the environment physically or materially and the myth contained in it is people who do damage both physically and non-physically in the sense of someone who experiences moral and moral depravity because advice and warning do not want to be heard anymore.